Hajj, Istita'ah, and Waiting List Regulation in Indonesia - Huda, Qomarul; Haeba, Ilham Dwitama (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study examines the concept of istita'ah (capability), and the problems faced by pilgrims in Indonesia with the departure regulation that implements a waiting list system. This research is purely a literature study using a normative juridical approach. Islamic law stipulates that one of the conditions that must be met by someone who will perform the pilgrimage is istita'ah (capable) which includes aspects of physical and spiritual health, financial ability, and safe situation. Unfortunately, even though these conditions have been met, it does not necessarily allow someone to go directly to Mecca to perform the pilgrimage. The reason is that there is a quota system set by the Saudi Arabian Government to balance the coming pilgrims with the capacity of the holy cities of Mecca and Medina. As a result of this quota system, prospective pilgrims in Indonesia have to queue waiting for departure, with a waiting time span of tens of years. This study finds out that the waiting list system, although aimed at ensuring the smooth and comfortable in performing pilgrimage, turned out to be an obstacle, because there is no guarantee that a person, in such a long waiting period, will remain healthy, even many. some of them had died before the time of departure arrived. Therefore, the government must find a solution to suppress the waiting list so that it does not continue to extend, by setting certain criteria for individuals who will register, for example the age limit and whether or not the person has performed hajj before.